The Casual Vacancy - Rowling, J. K. (New York : Little, Brown and Co., 2012)
The early death of a small town councilman reveals deep-rooted conflicts in the seemingly idyllic community of Pagford, which rapidly deteriorates in the face of cultural disputes, generation clashes, and a volatile election.
Keywords: City and town life -- Fiction -- England; Elections -- Fiction; England -- Fiction